2002
DOI: 10.1097/01.lab.0000017365.18894.d3
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Regulation of Connective Tissue Growth Factor on Hepatic Stellate Cells

Abstract: SUMMARY:Connective tissue growth factor (CTGF) is a 38-kd protein involved in several human fibrotic disorders including atherosclerosis and skin and renal fibrosis. Although it has been shown that human and experimental liver fibrosis is associated with CTGF expression through up-regulation of CTGF mRNA by hepatic stellate cells (HSC), the role of CTGF in the liver has not yet been determined. The aim of the present study was to assess the effects of CTGF on rat primary HSC and its regulation in a well-establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
129
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(140 citation statements)
references
References 23 publications
10
129
0
1
Order By: Relevance
“…Accumulating evidence has suggested that upregulation of CTGF might be a central pathway during HSC activation and hepatic fibrogenesis by mediating many of the profibrotic effects of TGF-␤ (1,41,42,53). CTGF expression in HSCs is significantly enhanced during the process of activation in vitro and in vivo (41,53). HSCs are the major cellular source of CTGF in the liver during liver fibrogenesis (42).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence has suggested that upregulation of CTGF might be a central pathway during HSC activation and hepatic fibrogenesis by mediating many of the profibrotic effects of TGF-␤ (1,41,42,53). CTGF expression in HSCs is significantly enhanced during the process of activation in vitro and in vivo (41,53). HSCs are the major cellular source of CTGF in the liver during liver fibrogenesis (42).…”
mentioning
confidence: 99%
“…HSCs are the major cellular source of CTGF in the liver during liver fibrogenesis (42). In response to exogenous CTGF, HSCs demonstrate increased migration, proliferation, adhesion, and expression of type I collagen (6,41). Blockade of CTGF synthesis by antisense oligonucleotides of CTGF resulted in downexpression of type I collagen mRNA in an animal model with experimental liver fibrosis (52).…”
mentioning
confidence: 99%
“…In fibrotic livers, CTGF is predominantly expressed in HSCs and bile duct epithelial cells. In cultured HSCs, CTGF expression is increased in activated HSCs and in HSCs treated with TGF-b [36]. PDGF also stimulates the production of CTGF by HSCs, an effect that is blocked by neutralization of TGF-b [36].…”
Section: Mediators That Stimulate Production Of Extracellular Matrix mentioning
confidence: 83%
“…In cultured HSCs, CTGF expression is increased in activated HSCs and in HSCs treated with TGF-b [36]. PDGF also stimulates the production of CTGF by HSCs, an effect that is blocked by neutralization of TGF-b [36]. Treatment of HSCs with CTGF stimulates collagen production and HSC proliferation and migration [36].…”
Section: Mediators That Stimulate Production Of Extracellular Matrix mentioning
confidence: 99%
See 1 more Smart Citation